Hollow fiber gas-liquid membrane contactors for acid gas capture - Ismail, Ahmad Fauzi (Penerbit UTM, 2007)
It is important to devise techniques which would reduce acid gases like CO2, H2S and other sulphoric components arising from the combustion of fossil fuels, present in natural gas, industrial gas and domestic processes effluent gas. They may have to be removed from the gas streams for environmental, economical and operational reasons. Efficient and flexible technologies capable to remove acid gases are needed operating over a wide range of concentration levels and a wide range of volumetric flow rates. Conventional industrial methods to reduce acid gases employ gas absorption devices like packed towers, spray towers, venture scrubbers, bubble column etc. In these devices gas-liquid contacting is achieved by dispersing the gas phase in the liquid phase to obtain large contact areas thereby increasing the mass transfer rate. Even though these contacting methods are very popular in industry they have several drawbacks such as difficulty of obtaining an accurate estimate of the gas-liquid mass transfer area and a limited range of gas and liquid flow rates due to operational problems.